Evaluasi Dampak Kebijakan Pengelolaan Lingkungan Bagi Masyarakat di Kawasan Industri Penyamakan Kulit Kabupaten Garut: Evaluating the Impact of Environmental Management Policies on Communities in the Leather Tannery Industrial Area of Garut Regency - Salwa Nurfaiziya; Sinta Ningrum; Mas Dadang Enjat Munajat; Heru Nurasa (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Industrialization fundamentally aims to enhance the quality of life and the welfare of people. However, insufficient management of residual production waste generates adverse effects on both the environment and the inhabitants residing near industrial zones. In response, the government has established regulatory measures for environmental protection and management through Government Regulation Number 22 of 2021. This regulation seeks to strike a balance between the community’s economic interests and environmental sustainability, safeguarding the rights of citizens. The core objectives of this research are to assess the state of environmental policies within the Sukaregang leather tanning industrial area, to scrutinize the implementation of environmental management practices, and to evaluate the impact of Government Regulation Number 22 of 2021. Employing a qualitative case study approach, the research centers on the Sukaregang leather tanning industrial area, a pivotal hub for the leather industry and a symbol of the Garut Regency. The data collection involves interviews with key stakeholders, including the Environmental Service, the leather tanning industry, and the affected community. The research concludes that while policies based on Government Regulation Number 22 of 2021 are in place, complementary local regulations are absent. The current implementation of environmental management continues to engender negative externalities in sectors such as agriculture, health, and environmental pollution. To address the shortfalls in achieving policy goals and objectives, it becomes imperative to establish local regulations that facilitate cost-sharing in the waste treatment process, utilizing Wastewater Treatment Plant (WWTP) technology. Such measures are essential for upholding environmental quality for the residents of industrial areas.